Does Long-Term Care Subsidisation Reduce Unnecessary Hospitalisations? - Joan Costa-i-Font; Sergi Jimenez-Martin; Cristina Vilaplana (Center for Economic Studies and ifo Institute (CESifo), 2016)
The expansion of long-term care (LTC) coverage may improve health system efficiency by reducing hospitalisations (bed-blocking), and pave the way for the implementation of health and social care coordination plans. We draw upon the quasi-experimental evidence from the main expansion of long term care increase subsidisation in Spain in 2007 to examine the causal effect of the expansion of LTC subsidisation and coordination on hospitalisations (both on the internal and external margin) and the hospital length of stay. In addition, we examine the 2012 austerity budget cuts that reduced the subsidy. We find robust evidence of a reduction in hospitalisations and the length of stay after the expansion of LTC subsidisation. However, the reduction in hospitalisations is heterogeneous to the existence of health and social care coordination plans and type of subsidy. Overall, we estimate savings related to hospitalisations of up to 11% of total hospital costs. Consistently, subsidy reduction is found to attenuate bed-blocking gains.
Keywords: I18; J14; H53; 330; hospitalisation; long-term care reform; Spain; bed-blocking; hurdle Poisson model